Digital Q-Control and Automatic Probe Landing in Amplitude Modulation Phase Imaging AFM Mode. Issue 1 (July 2017) - Belikov, Sergey; Alexander, John; Surtchev, Marko; Magonov, Sergei
Abstract: We present a new digital design of Q-control, i.e. controllable change of cantilever quality factor, targeted for digital implementation at an FPGA. The designed Q-controller changes the amplitude and phase of cantilever excitation based on amplitude and phase of the deflection signal measured by a digital lock-in amplifier. This significantly differs from the conventional design, where effective Q-factor is modified by adding a self-excitation force proportional to the cantilever deflection of an earlier time. Our new digital Q-control algorithm is justified by flexible beam asymptotic models based on the Euler-Bernoulli equation and the Krylov-Bogoliubov-Mitropolsky averaging technique. Many controversial features of Q-control can now be verified by models. By contrast with conventional implementation that requires additional analog electronics, our design is implemented at an FPGA in parallel with many other control and signal processing algorithms. The ability of Q-control to decrease tip-sample interaction with a higher effective Q and increase it with a lower one is illustrated on automatic landing (soft approach) of the tip with minimal indenting of the sample surface, or damage to the tip.